Intelligent Internationalization The Shape of Things to Come. - Godwin, Kara A. (Global Perspectives on Higher Education Ser., 2019)
"In 2015, Laura Rumbley put forward the notion that higher education-in a highly complex, globally interdependent world-would be wise to commit to an agenda of "intelligent internationalization" (I2). I2 turns on the notion that "the development of a thoughtful alliance between the research, practitioner, and policy communities," in tandem with key decision makers in leadership roles, is essential for institutions and systems of higher education seeking sustained relevance and vitality through their internationalization efforts. Does "intelligent internationalization" make sense? What is faulty, misguided, or missing from this analysis that could be strengthened through further consideration? On the other hand, what speaks to its value as an idea or agenda to advance the way that internationalization is understood and enacted in the world? These issues will be addressed in this book which builds on a 2018 Symposium on Intelligent Internationalization".